Distillery Spentwash Irrigation on the Yields of Radish (Raphanus sativus), Onion (Allium cepa) and Garlic (Allium sativum) - Chandraju, S.; Nagendraswamy, R.; Chidankumar, C.S.; Nagendraswamy, Girija (Asian Journal of Chemistry, 2010)
Cultivation of radish (Raphanus sativus), onion (Allium cepa) and garlic (Allium sativum) medicinal plants was made by irrigation with distillery spentwash of different dilutions. The spentwash i.e., primary treated spentwash and 33 % spentwash were analyzed for their plant nutrients such as nitrogen, phosphorous, potassium and other physical and chemical parameters. Experimental soils i.e., normal soil (plot-1) and spentwash treated (plot-2) soils were tested for their chemical and physical parameters. The seeds (Namadhari and Mayhco) were sowed in the prepared land and irrigated with raw water and 33 % spentwash. Influence of spentwash in normal and spentwash treated soils on the yields were investigated at their respective maturity. It was found that the yields of all plants were high in 33 % than raw water irrigation. Further, the yields were very high in spentwash treated soil (plot-2) than normal soil (plot-1) and raw water irrigations all plants.